Multiomic analysis reveals developmental dynamics of the human heart in health and disease - James Cranley; Kazumasa Kanemaru; Semih Bayraktar; Vincent Knight-Schrijver; J. Patrick Pett; Krzysztof Polański; Monika Dabrowska; Ilaria Mulas; Laura Richardson; Claudia I. Semprich; Rakeshlal Kapuge; Shani Perera; et al. (2024)
Abstract Developmental dynamics encompass both the specification of cell types and their spatial organisation into multicellular niches. Here we harness the power of single-cell and spatial multiomics to unravel embryonic and foetal cardiac tissue niches, which lead to the development of a new tool, TissueTypist. We reveal that cardiac-resident macrophages likely originate from the yolk sac, forming heterogeneous subsets. CX3CR1 + macrophages with a microglia-like profile localise in the sinoatrial node, which may contribute to axon guidance for the innervating autonomic neurons. Foetal pacemaker cells exhibit distinct characteristics compared to their adult counterparts, including the expression of genes that are known to promote parasympathetic innervation. We highlight the enhancer-mediated gene regulatory networks governing atrial and ventricular cardiomyocyte specification. The maturation of atrial cardiomyocytes into distinct left and right phenotypes, driven by transcription factors linked to atrial septal defect genes, underscores the significance of this process for healthy heart development. In the ventricle, cellular and transcriptional gradients along both pseudotime and the transmural axis provide a new molecular understanding of myocardial compaction. Finally, generating data from Trisomy 21 hearts and comparing this with the euploid atlas, we reveal a reduced abundance of specific cell types including compact cardiomyocytes. Overall, this extensive dataset and our precomputed models will form a valuable resource for the field.